PENGARUH TINGKAT PRODUKTIVITAS HASIL TANI PADI TERHADAP KONDISI EKONOMI DI DESA BENU KECAMATAN TAKARI KABUPATEN KUPANG - Naisumu, Mira Fransiska; Sunimbar, Sunimbar; Manek, Agustinus Hale (Universitas Nusa Cendana, 2022)
This study aims to determine (1) effect of factors for productivity of rice yields in Benu Village, Takari District, Kupang Regency (2) The effect of rice productivity on the economic condition of the community in Benu Village, Takari District, Kupang Regency. This research is a quantitative description research. The process of determining respondents in the study used random sampling with a total of 59 respondents. Data collection techniques in this study used two techniques, are questionnaires and documentation. The data analysis techniques used quantitative descriptive analysis techniques and simple regression analysis. Based on the research results, the geographical factors that affect the productivity of rice farming in Benu Village are climatic conditions, soil conditions, types of land and types of irrigation channels that play an important role in agriculture. The effect of rice productivity on economic conditions can be seen by the T test (partial test) it can be seen that the variable level of agricultural productivity (x) shows a significant value < (0.004 < 0.05) with a B value of -0.371 which means that the level of productivity rice farming has a positive and significant effect on economic conditions in Benu Village, Takari District, Kupang Regency. In the table of the coefficient of determination, it can be seen that the R value of 0.371 indicates that the effect of the level of productivity of agricultural products on economic conditions in Benu Village, Takari District, Kupang Regency is 37% while the remaining 63% is explained by variables that do not exist in the study such as employment status and other income. . And in the regression test a significant value of 0.004 <0.05 indicates a positive and significant influence on economic conditions in Benu Village, Takari District, Kupang Regency.